Analysis of conjugate heat transfer in a roots blower and validation with infrared thermography. (November 2022) - Matuzović, Mario; Rane, Sham; Patel, Brijeshkumar; Kovačević, Ahmed; Tuković, Željko
Highlights: Conjugate heat transfer in a Roots blower. Gap size calibration achieved deviation of 7.5% on flow and 4.3% on power. Discharge air temperature deviation was within 4 °C. High speed infrared thermography based surface temperature deviation was within 6 °C. Abstract: Oil-free Roots blower is a type of Positive Displacement Machine used for low pressure ratio applications. Its volumetric efficiency is dependent on the leakage of compressed gas through the clearance gaps. In the absence of internal cooling, prediction of temperature distribution and conjugate heat transfer becomes important for reliable design and operation. The interaction of gas flow and structural deformation in the blower is highly transient and one of the most challenging problems which need to be addressed for accurate performance prediction. To achieve this, the technique which includes moving and transforming the mesh is employed. The performance test data used for validation included discharge air temperature, mass flow rate, pressure, and power. The comparison between numerical and experimental results has shown good agreement of 7.5% on flow, 4.3% on power while the discharge temperature deviation was within 4°C. High speed infrared thermography of the rotor lobe and housing surface temperatures was used to evaluate the accuracy of the Conjugate Heat Transfer model. The difference between the experiment and simulation was within 6°C. The aim of this study was to develop and validate the numerical model for analysis of heat transfer between pressurized air and compressor elements and to provide temperature distribution in structural elements. By this means, the operational gap sizes can be reliably minimised during the design of a machine. Graphical abstract: Image, graphical abstract